WHO Video Advertisement Staying Mentally Healthy-Beat Covid-19: A Semiotic Study (e-Journal of Linguistics, 2025)
This study entitled WHO Video Advertisement “Staying Mentally Healthy – Beat Covid-19”: A Semiotic Study. The study aims to analyze the verbal and visual signs in this advertisement and also to identify the meaning of the signs. This study uses qualitative method to conduct a clear and well-organized description about the problems which is identified. The data were taken from YouTube audiovisual uploaded by World Health Organization (WHO) and analyzed by applying theory proposed by Saussure (1983), and theory of meaning by Barthes (1964), followed by supporting theory of color term by Wierzbicka (1996). The result of the study mentioned that verbal signs used as media to inform and emphasize the persuasive expression to people about a positive message from the advertiser. Meanwhile, the nonverbal signs contained conceptual and hidden meaning to beautify the advertisement and attract the audience attention. The characteristics of verbal signs occurred in form of word phrases and sentences while visual signs can be analyzed from the cartoon illustration, inanimate objects, and gestures